Use of extracellular extracts of lactic acid bacteria and bifidobacteria for the inhibition of dermatological pathogen Staphylococcus aureus - Yan Yan Hor; Min Tze Liong (Wolters Kluwer Medknow Publications, 2014)
Background/Objectives: The application of lactic acid bacteria (LAB) and bifidobacteria, which exhibit therapeutic benefits, in dermatology, including treatment of skin infections specifically caused by Staphylococcus aureus, is new. The objectives of this study were to screen LAB and bifidobacteria for antimicrobial activity against S. aureus and to identify the antimicrobial compounds produced by LAB. In addition, the study aimed to inhibit the biofilm of S. aureus with extracellular extracts of LAB. Methods: A total of 87 strains of LAB and three strains of bifidobacteria, grouped according to their respective origins, were screened for antimicrobial activity against S. aureus using the cell-free supernatant (CFS). Antimicrobial activity of the CFS was evaluated following neutralization, protease treatment, and protein precipitation treatment. Characterization was performed to identify the antimicrobial compounds in the CFS. Inhibition of the S. aureus biofilm was assessed with a crystal violet assay. Results: LAB and bifidobacteria inhibited the growth of S. aureus, with percentage of growth inhibition ranging from 0.5% to 34.2%. All strains demonstrated a drastic reduction (p < 0.05) in growth inhibition upon neutralization. Antimicrobial compounds in the CFS were lactic acid, acetic acid, hydrogen peroxide, and diacetyl. The CFS of strain Lactobacillus bulgaricus FTDC 8611 significantly hindered (p < 0.05) the biofilm formation of S. aureus. Statistical analysis was performed with SPSS version 19.0. Conclusion: LAB were able to produce antimicrobial compounds that inhibit S. aureus. The inhibitory action of the CFS was mainly due to the organic acids produced by LAB. Antimicrobial metabolites produced by LAB comprise lactic acid, acetic acid, hydrogen peroxide, and diacetyl. S. aureus was able to form a biofilm, which was successfully inhibited by the CFS of L. bulgaricus FTDC 8611.